Are younger cohorts in the USA and England ageing better?. (25th June 2019) - de la Fuente, Javier; Caballero, Francisco Félix; Verdes, Emese; Rodríguez-Artalejo, Fernando; Cabello, María; de la Torre-Luque, Alejandro; Sánchez-Niubó, Albert; María Haro, Josep; Ayuso-Mateos, José Luis; Chatterji, Somnath
Abstract: Background: Whether worldwide increases in life expectancy are accompanied by a better health status is still a debate. People age differently, and there is a need to disentangle whether healthy-ageing pathways can be shaped by cohort effects. This study aims to analyse trends in health status in two large nationally representative samples of older adults from England and the USA. Methods: The sample comprised 55 684 participants from the first seven waves of the English Longitudinal Study of Ageing (ELSA), and the first 11 waves of the Health and Retirement Study (HRS). A common latent health score based on Bayesian multilevel item response theory was used. Two Bayesian mixed-effects multilevel models were used to assess cohort effects on health in ELSA and HRS separately, controlling for the effect of household wealth and educational attainment. Results: Similar ageing trends were found in ELSA (β   =  – 0.311; p  <   0.001) and HRS (β   =  – 0.393; p  <   0.001). The level of education moderated the life-course effect on health in both ELSA (β   =  – 0.082; p  <   0.05) and HRS (β   =  – 0.084; p  <   0.05). A birth-year effect was found for those belonging to the highest quintiles of household wealth in both ELSA (β = 0.125; p  <   0.001) and HRS (β = 0.170; p  <   0.001). Conclusions: Health inequalities have increased in recent cohorts, with the wealthiest participants presenting a better health status in both the USA and English populations. Actions to promote health in the ageing population should consider the increasing inequality scenario, not only by applying highly effective interventions, but also by making them accessible to all members of society.